2005
DOI: 10.1111/j.1365-2338.2005.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

On the presence and distribution of olive viruses in Lebanon

Abstract: A survey for viruses was carried out in 2003 in the main olive‐growing areas of Lebanon (South Lebanon, North Lebanon, Mount Lebanon and Bekaa). A total of 300 samples was collected in 31 different locations in 76 different commercial orchards and checked by RT‐PCR for the presence of Arabis mosaic virus (ArMV), Cherry leaf roll virus (CLRV), Strawberry latent ringspot virus (SLRV), Olive latent virus 1 (OLV‐1) and Olive leaf yellowing‐associated virus (OLYaV), using virus‐specific primers reported in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 6 publications
3
20
1
Order By: Relevance
“…(2004), with a mean infection rate of 49.1% (Table 2), a value slightly higher than that previously reported from other Mediterranean countries, i.e., Lebanon (23.6%) and Syria (14.5%) (Al Abdullah et al. 2005; Fadel et al. 2005).…”
Section: Resultsmentioning
confidence: 58%
“…(2004), with a mean infection rate of 49.1% (Table 2), a value slightly higher than that previously reported from other Mediterranean countries, i.e., Lebanon (23.6%) and Syria (14.5%) (Al Abdullah et al. 2005; Fadel et al. 2005).…”
Section: Resultsmentioning
confidence: 58%
“…OLV-2 was isolated by mechanical inoculation from symptomless olive trees in Apulia, Southern Italy (Savino et al, 1984). It has subsequently been identified in Lebanon (Fadel et al, 2005), Syria (Alabdullah et al, 2005), Croatia (Bjelis et al, 2007) and Tunisia (Martelli, 2011) from symptomless olive cultivars. The host range of OLV-2 was limited to olive trees until castor beans (Ricinus communis L.), showing yellowish vein netting and systemic mottling on leaves, were reported in Greece to be infected with this virus (Grieco et al, 2002).…”
Section: Strawberry Latent Ringspot Virus (Slrsv)mentioning
confidence: 99%
“…The OLY syndrome, consisting of poor fruit set, bright yellow discoloration of the foliage, mottling, necrosis, extensive defoliation and dieback, has been associated to other viruses such as Olive vein yellowing associated virus (OVYaV) (Faggioli & Barba, 1995) and Olive yellow mottle and decline associated virus (OYMDaV) , but their presence on olive trees was very rare. On the other hand, OLYaV seems to be one of the most widespread olive viruses: in Italy it infects more than 60% of southern Italy olive cultivars (Faggioli et al, 2005) and it has also been reported in high percentages in Israel (Martelli, 2011), Egypt, USA (Saponari & Savino, 2003), Lebanon (Fadel et al, 2005), Spain (Martelli, 2011), Syria (Alabdullah et al, 2005), Albania (Luigi et al, 2009), Croatia (Bjelis et al, 2007, Tunisia (Martelli, 2011) and California (Al Rwahnih et al, 2011). A study on the rooting and grafting capacity of OLYaV-infected 'Carolea' and its respective healthy controls showed that the virus does not influence the rate of rooting of the cuttings and does not interfere with the grafting success rate; positive significant effects in grafting ability were observed on infected material only during a temperature stress, probably due to the reduced water need of infected shoots (Roschetti et al, 2009).…”
Section: Strawberry Latent Ringspot Virus (Slrsv)mentioning
confidence: 99%
See 2 more Smart Citations